The Relationship Between Self Care and Juvenile Delinquency in Volleyball Class Students of State Madrasah Aliyah 5 Ciamis in the 2025/2026 Academic Year - Siti Aulia Rohmah; Yandi Cahya Yundani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study aims to determine the relationship between self-care and juvenile delinquency among volleyball students at Madrasah Aliyah Negeri 5 Ciamis in the 2025/2026 academic year. This study used a quantitative descriptive method with a Likert-scale questionnaire administered to 66 respondents. The results showed that students' self-care levels were in the moderate (57.58%) and high (42.42%) categories, while their juvenile delinquency levels were in the moderate (65.15%) and high (34.85%) categories. Normality tests showed that both variables were normally distributed, and linearity tests indicated a linear relationship with a significance value of 0.0017. Correlation tests showed a coefficient of 0.3778, which is in the low to moderate category. Therefore, it can be concluded that there is a relationship between self-care and juvenile delinquency, with good self-care tending to be associated with lower levels of juvenile delinquency, although the relationship is not very strong.